An Analysis of Inventory Management at DAMN!I LOVE INDONESIA - Purnama, Annisa; Simatupang, Togar M (Journal of Business and Management, 2013)
Damn! I love Indonesia is a company engaged in fashion industry. It is a local clothing brand in Indonesia with Indonesian culture as a themed. They package the Indonesian culture with a modern or urban way. Damn! I love Indonesiaâ€™s goal is to ignite the nationality and to embrace our identity. Besides that, this company purpose is to bring young generation to love and recognize Indonesian culture, as well as to recall the history of Indonesia. This company vision is to grow the sense of pride, love, spirit and patriotism of young generation of our country, and to ignite their nationalism, while the mission is to be a leading and a largest Indonesia urban brand in clothing and accessories industry. In running the business, Damn! I love Indonesia uses T-shirt as the main product to raise the sales. Compared to other product in Damn! I love Indonesia, T-shirt have the largest proportion about 70% of total sales. However, the existence of T-shirt is very important for Damn! I love Indonesia. At this time, Damn! I love Indonesia face the problem that deals with inventory management of T-shirt. This research is aimed for reviewing business process, finding the root cause of the problem occurred in Damn! I love Indonesia and create a solution map. Business process is used for identifying all the process that is been done in Damn! I love Indonesia. By describing each process, root causes of the problem can be made and analysed. There are four root causes occur in Damn! I love Indonesia. Those root cause are no market intelligence, promotion is not aligned to forecast, inaccurate forecast method, and vendor cannot fulfil order expectation. To solve those problems, there are some proposed solutions given. Those solutions made in form of solution map. The first solution is improving the market intelligence. Next problem can be solved by share promotion plan with production division. Using appropriate forecasting method and combine with subjective prediction will be the next solution. The last is making a new timeline and regulation for a vendor.Â Keywords: Inventory Management, Forecasting, Business Process, Root Cause Analysis, Solution Map, Damn! I love Indonesia, T-shirt.